Ketorolac and Hematoma Incidence in Postmastectomy Implant-Based Breast Reconstruction. Issue 5 (May 2018) - Mikhaylov, Yana; Weinstein, Brielle; Schrank, Travis P.; Swartz, Jennifer D.; Ulm, Jason P.; Armstrong, Milton B.; Delaney, Kevin O.
Abstract : Background: Ketorolac tromethamine (Toradol) is an effective a nonsteroidal anti-inflammatory drug and a powerful analgesic for patients undergoing breast surgery. However, the potential for postoperative bleeding has not yet been explored specifically in women undergoing implant-based breast reconstruction. There is concern that an increased risk of bleeding exists in this population due to the lack of tissue apposition as a result of implant placement. We therefore seek to assess the associated risk of bleeding complication in implant-based breast reconstruction at our academic institution. To the best of our knowledge, this represents the first case series addressing safety profile of Toradol specifically in patients undergoing nonautologous, implant-based breast reconstruction. Methods/Results: A single-center, retrospective review was performed analyzing our institutional experience with Toradol in nonautologous, implant-based breast reconstruction following mastectomy. A prospective database of 522 patients collected between 2008 and 2013 was analyzed. Within the database, 57 patients who received intraoperative ketorolac were identified among a total of 180 patients undergoing prosthetic reconstruction. No statistically significant difference was found in the incidence of clinically relevant hematoma formation between the control and Toradol groups. The frequency of hematoma formation in the control was 0.09 (11/123 patients, 95% confidence interval = 0.05–0.15) and 0.04 in the Toradol group (2/57 patients, 95% confidence interval = 0.01–0.12), resulting in a P value of 0.32. Regarding the secondary outcomes, we did not detect a statistically significant difference in the total number of complications or length of hospital stay in the Toradol and control groups. Conclusions: Review of our breast reconstruction database did not find a trend toward an elevated incidence of hematoma associated with intraoperative Toradol use in implant-based postmastectomy reconstruction.